2020
DOI: 10.18280/ijht.380202
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of the Airflow Structure in a Solar Chimney

Abstract: Solar chimney converts solar thermal energy into kinetic energy to generate electricity and it is an alternative technology for electricity generation from solar energy. In this work, we are interested in the study of geometrical parameters on convection airflow within a solar chimney. For this, we have considered a two-dimensional prototype model of a solar chimney. The boundary conditions are chosen to be similar to those in reality. The considered mathematical model is a system of partial differential equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In computation the number and the form of the control volume constructed the computational domain have a great influence on the precision of the results and the calculation time [20][21][22]. To explore the effect of mesh spacing on numerical solutions, we tested three uniform meshes: 42 3 , 62 3 , 82 3 nodes.…”
Section: Effect Of Mesh Spacingmentioning
confidence: 99%
“…In computation the number and the form of the control volume constructed the computational domain have a great influence on the precision of the results and the calculation time [20][21][22]. To explore the effect of mesh spacing on numerical solutions, we tested three uniform meshes: 42 3 , 62 3 , 82 3 nodes.…”
Section: Effect Of Mesh Spacingmentioning
confidence: 99%
“…The solar chimney is a feasible passive solar heating and cooling solution that uses clean energy rather than fossil fuels [1,2]. Solar radiation is used to boost the temperature of the air, and the buoyancy of warm air is used to speed up the airflow through the system [3][4][5]. The solar chimney is the subject of many studies that have shown how the use of PCM improves its thermal performance, where it is highlighted how the thermal and geometric features of PCMs have a significant impact on overall chimney performance.…”
Section: Introductionmentioning
confidence: 99%